Digital retinopathy photography: the way forward for standardizing retinal screening in patients living with diabetes: an overview of the key challenges to care delivery in Qatar - Amin, Sheetal Rajnikant; Shah, Benazir (International Journal of Research in Medical Sciences, 2023)
The incidence of diabetes is rising globally with Qatar being ranked as the 3rd highest country for the prevalence of diabetes in the Middle East and North African (MENA) region. Diabetic retinopathy (DR) is the main cause of sight-threatening complications of diabetes. Significant advances in screening and treatment for DR have emerged in the last few decades with a strong impact on the accuracy and effectiveness of screening. DR being a preventable cause of blindness with early detection and interventions like laser photocoagulation and anti-vascular endothelial growth factor (anti-VEGF) treatments makes it imperative to invest in early recognition and treatment for DR. Globally screening is done by direct/indirect ophthalmoscopy or retinal photography with huge variations in early diagnosis. Studies have revealed the superiority of three-field retinal photography when compared to direct ophthalmoscopy, for DR screening, even if performed by an experienced ophthalmologist. The two most sensitive means of detection at present are digital retinal imaging and slit lamp examination post mydriasis. Both modalities require assessment by trained personnel. Digital retinal photography is extremely quick, allows the creation of permanent records and with the advent of semiautomatic nonmydriatic cameras, requires less skill as compared to the use of a slit lamp. Hence, should digital retinal photography be a preferred standardised method for retinal screening in Qatar?